Topical issues of legal principles of state in Ukraine - Хорт, Ігор Володимирович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2010)
The author considers in the article the principles of the legal state. The author pays attention to the mechanism of realization of such principles as supremacy of right, division of power, reality of rights and freedoms of man and citizen, legality, effective activity of organs of power.